2022
DOI: 10.1167/iovs.63.5.29
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Adaptation to Continuous Versus Intermittent Exposure to Spatial Distortions

Abstract: Purpose To examine perceptual adaptation when people wear spectacles that produce unequal retinal image magnification. Methods Two groups of 15 participants (10 male; mean age 25.6 ± 4.9 years) wore spectacles with a 3.8% horizontal magnifier over one eye. The continuous-wear group wore the spectacles for 5 hours straight. The intermittent-wear group wore them for five 1-hour intervals. To measure slant and shape distortions produced by the spectacles, participants adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In both experiments, experience with an environmental change allowed the visual system to adjust to that change more rapidly and strongly across days. Experiment 1 demonstrated that a once-daily experience is sufficient for such an effect, with no need for multiple switches between different environments (see McLean et al [2022] for a similar investigation into 5-hr vs. five 1-hr periods for a single day of adaptation to monocular magnification). Experiment 2 showed that the effect of mode switching applies to many stimuli in a given environment, causing them to appear more and more normal over time, at roughly equal speed.…”
Section: Discussionmentioning
confidence: 94%
“…In both experiments, experience with an environmental change allowed the visual system to adjust to that change more rapidly and strongly across days. Experiment 1 demonstrated that a once-daily experience is sufficient for such an effect, with no need for multiple switches between different environments (see McLean et al [2022] for a similar investigation into 5-hr vs. five 1-hr periods for a single day of adaptation to monocular magnification). Experiment 2 showed that the effect of mode switching applies to many stimuli in a given environment, causing them to appear more and more normal over time, at roughly equal speed.…”
Section: Discussionmentioning
confidence: 94%
“…The extent of adaptation to all these effects at any given time will likely contribute to different symptom arrays. Further, the type of adaptation may differ depending on whether the device is worn continuously or across intermittent periods ( Li, Tregillus, & Engel, 2022 ; Li, Tregillus, Luo, & Engel, 2020 ; McLean, Manning, & Cooper, 2022 ). Understanding the adaptation of phenomena that underlie dominant symptoms like visual swim and dizziness could be a fruitful way to investigate the long-term effects of optical distortions.…”
Section: Discussionmentioning
confidence: 99%